Comparative study of magnetic pc 1 pulsations observed at low and high latitudes: Long-term variation of occurrence frequency of the pulsations - Kawamura, Makoto; Kuwashima, Masayuki; Toya, Takeshi; Fukunishi, Hiroshi (1983)
P(論文) Main purposes of this study are to clarify source region and generation mechanism of periodic emissions by means of comparison of characteristics of the emissions observed at high and low latitudes. In the present paper, long-term variations of the occurrence at Syowa Station and Memambetsu during five years from 1976 to 1980 are investigated statistically. It is an important result obtained from the investigation that the variation has a clear reverse relation to that of the relative sunspot number, that is, the occurrence decreases with increase of the solar activity. More intense attenuation of the emissions in the ionospheric duct in such active years will be regarded as the main cause of the decrease. Because of inward shift of the plasmapause, the wave-particle interaction caused by ring-current protons will also hardly occur statistically in the active years. In other words, the long-term variation can also be explained well by the mechanisms of generation and propagation of the emissions proposed already by the same authors. As an only event in 1980,periodic emissions with unusual low frequency were observed successively at Memambetsu throughout the day of December 20. As the frequency seems to be fairly lower than the cutoff frequency of the ionospheric duct, the emissions will be unable to propagate through the duct. Therefore, the source latitudes will be located near Memambetsu. The generation may be related to another exciting mechanism such as helium cyclotron resonance. departmental bulletin paper